Distance‐adaptive routing and spectrum assignment in rings. Issue 3 (1st May 2016) - Talebi, Sahar; Katib, Iyad; Rouskas, George N.
Abstract : Distance adaptive spectrum allocation exploits the tradeoff between spectrum width and reach to improve resource utilisation by tailoring the modulation format to the level of impairments along the path. The authors first show that the distance‐adaptive routing and spectrum assignment (DA‐RSA) problem is a special case of a multiprocessor scheduling problem. The authors then develop a suite of efficient and effective DA‐RSA algorithms for ring networks, that build upon list scheduling concepts. This work explores the tradeoffs involved in DA‐RSA algorithm design, and opens up new research directions that may leverage the vast literature in scheduling theory.